Application of the Teams Games Tournament Cooperative Learning Model to Improve Mathematics Learning Outcomes of Grade V Students at UPTD SD Negeri 136 Barru - Usman; Zaid Zainal; Alfiana (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Low mathematics achievement among Grade V students at UPTD SD Negeri 136 Barru was associated with limited classroom participation, textbook-dominated instruction, infrequent collaborative activities, and low learning motivation. This study aimed to examine the implementation of the Teams Games Tournament (TGT) cooperative learning model and its effectiveness in improving the mathematics learning process and student achievement. Classroom action research employing a mixed-methods approach was conducted with one teacher and 21 students. Data were collected through observation, achievement tests, and documentation and analyzed using qualitative and quantitative descriptive techniques, including data condensation, data display, and conclusion drawing. The intervention was considered successful when teacher and student learning activities reached the Good (B) category and at least 76% of students achieved learning mastery. The findings showed that teacher and student activities improved from the Fair (C) category in Cycle I to the Good (B) category in Cycle II. The proportion of students achieving mastery also increased from 62% in Cycle I to 80% in Cycle II. These findings demonstrate that the TGT cooperative learning model effectively improved both the instructional process and mathematics learning outcomes of Grade V students. The study provides practical evidence that structured team-based competition can promote active participation, collaborative learning, and improved mathematics achievement in primary education.